Do sexes differ in consistent individual differences and behavioural syndrome in an aposematic poison frog? - Cossio, R.; Ibáñez, R.; Rodríguez, A.; Pröhl, H. (Journal of zoology (1987), 2024)
There is a burgeoning interest in studying consistent individual differences in animal behaviour. Most studies consider mainly males, but sexes are subject to distinct selection pressures that may drive differences in life history and therefore lead to differences in a variety of behaviours. Here, we used Oophaga pumilio, a poison frog with sex differences in life‐history strategies (e.g., sex bias in space use and parental care), to explore whether sexes differ or share personality characteristics like behavioural consistency and behavioural syndromes. Based on the natural history of this species, we predicted sex differences in behavioural consistency in exploration but not in boldness, and a correlation between these behavioural traits. We found no sex differences in behavioural consistency in boldness and exploration, although, we observed a tendency of higher consistency in males than females in boldness. When pooling all individuals, we found a higher consistency in boldness than exploration, suggesting the presence of a bold personality in general. We observed a positive between‐individual correlation of boldness and exploration in both sexes indicating the presence of a behavioural syndrome. Our data suggest that selective mechanisms shaping individual behaviour act equally on both sexes in this poison frog. We explore whether Oophaga pumilio exhibit sex differences in consistent individual differences in boldness and exploration, and a behavioural syndrome between these behaviours. We found no sex differences in behavioural consistency in boldness and exploration, but we demonstrate that our study population exhibit a bold personality trait that co‐varies with exploration.